2020
DOI: 10.3390/su12198041
|View full text |Cite
|
Sign up to set email alerts
|

Ethically Minded Consumer Behavior, Retailers’ Commitment to Sustainable Development, and Store Equity in Hypermarkets

Abstract: The present paper analyzed the influence of ethically minded consumer behavior on retailer’s commitment to sustainable development as perceived by the consumer, and their contribution to the chain of relationships “store equity–loyalty–word of mouth communication”, in the context of retailing. Responses from 317 hypermarket customers in Ecuador were analyzed. The model was estimated using the partial least squares technique. The results show the sustainable development actions implemented by retailers, togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…, 2015). Consumers show an emotional connection that is translated into positive attitudes; consumers' purchase, repeat purchase and intention to recommend (Cacho-Elizondo and Loussaïef, 2010), thus supporting the effect of sustainability on store equity (Marín-García et al. , 2019; Sánchez-González et al.…”
Section: Literature Reviewmentioning
confidence: 92%
See 3 more Smart Citations
“…, 2015). Consumers show an emotional connection that is translated into positive attitudes; consumers' purchase, repeat purchase and intention to recommend (Cacho-Elizondo and Loussaïef, 2010), thus supporting the effect of sustainability on store equity (Marín-García et al. , 2019; Sánchez-González et al.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Sustainable development emerges as an issue of global interest (Jin-Myong et al. , 2017; Chang and Chou, 2018; IISD, 2019), which involves social, economic and environmental sectors (Sánchez-González et al. , 2020a, b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers categorize loyalty into food brand loyalty, namely, the sustainable products offered by retailers, such as organic food. The analyzed studies suggested that this type of loyalty may be facilitated by attitudinal measures since the purchase of ethical and sustainable products reflected a strong attitude toward those brands that represented consumers' individual values [121][122][123][124]. This motivated consumers to buy more organic food than others [125][126][127].…”
Section: Untapped Loyalty At the Sustainability Levelmentioning
confidence: 99%